The Politics of Festival-Tracing the origin and growth of Karbi Youth Festival: Search for identity. - Teronpi, Bandita; Das, Dr. K.C. (IJRDO - Journal of Social Science and Humanities Research, 2016)
It takes ten years to grow a tree but it takes a hundred years to establish the identity of a people’-confusius. ‘Evens are now established method for promoting destination supplementing their traditional role as forms of exhibitions are performance’ (roche 2000).